Comparison of rates of infection of two methods of emergency ventricular drainage. Issue 4 (April 1995) - Kim, D K; Uttley, D; Bell, B A; Marsh, H T; Moore, A J
Abstract : The rates of infection of two methods of external ventricular drainage in use at Atkinson Morley's Hospital–namely, (a) percutaneous drainage with Rickham reservoirs and (b) tunnelled ventriculostomies–were compared in this retrospective review. Percutaneous drainage of CSF with Rickham reservoirs was associated with a 27% rate of infection as identified by positive microbiological cultures; tunnelled ventriculostomy catheters had a 10% infection rate. The difference in the infection rate between the two methods was statistically significant (P < 0.015). Other variables examined, including the age and sex of the patients and the reasons for ventricular drainage, were not associated with an increased rate of infection. Most infections from either method were caused by a coagulase negative staphylococcus. The average duration of ventricular drainage before identification of positive cultures was 5.7 days for Rickham reservoirs and 6.0 days for ventriculostomies.